A biorepository for the in‐depth validation of pre‐analytical sample handling effects on novel blood‐based biomarkers for Alzheimer's disease: The first results: Biomarkers (non‐neuroimaging): Method development and validation. (7th December 2020) - Verberk, Inge M.W.; Misdorp, Els O.; Koelewijn, Jannet MW; Shan, Dandan; Lambrechts, Charlotte; Shaw, Leslie M.; Rissman, Robert A.; Blennow, Kaj; Zetterberg, Henrik; Ball, Andrew J.; Edelmayer, Rebecca M.; Teunissen, Charlotte E.
Abstract: Background: Variation in pre‐analytical sample handling can critically affect biomarker concentrations in biofluids. A study on pre‐analytical effects on novel blood‐based biomarkers is therefore of importance to facilitate their swift introduction in clinical settings. Guided by the Alzheimer's Association, we established a biorepository of systematically "mistreated" blood samples for analysis of various biomarkers using various technologies. Here we present the first results. Method: Blood samples were collected from 90 volunteers presenting at the hospital for any disease. Blood was mistreated according to 8 pre‐analytical protocols, resulting in n=10 sample sets per protocol with several aliquots per set to be shared among labs for biomarker analysis. The protocols were designed to test the effects of type of collection tube, and the effects on K2‐EDTA plasma of delayed centrifugation (at room temperature (RT) or 4°C), centrifugation temperature (RT or 4°C), delayed freezing after centrifugation (RT or 4°C), two‐week intermittent storage at low temperature (4°C or ‐20°C), freezing‐thawing (up to 4x) and aliquot tube filling (250µl, 500µl or 1000µl in 1.5‐mL tube). Using a novel 4‐plex Simoa assay simultaneously measuring Abeta(1‐42), Abeta(1‐40), GFAP and NfL, we obtained the first results on our sample sets. A decline was regarded relevant when a change of at least a 10% was observed in the biomarker value compared to the reference conditions. Result: Collection tube type affected the levels of the assessed markers Abeta(1‐42/1‐40), GFAP and NfL (Figure 1). Delayed centrifugation affected only plasma Abeta(1‐42/1‐40), and only when kept at RT for 24h (average ‐18% decline compared to no delay) and not when kept at 4°C (Figure 2). This same pattern was observed for hold time after centrifugation (Abeta(1‐42/1‐40) : ‐16% for 24h hold at RT). Two‐week storage at 4°C but not at ‐20°C affected only Abeta(1‐42/1‐40) (average ‐15%). Centrifugation temperature, up to four freeze‐thaw cycles and aliquot tube filling did not affect the biomarker values Abeta(1‐42/1‐40), GFAP and NfL. Conclusion: These first results of the project on pre‐analytical effects on novel blood‐based biomarker concentrations show that relevant pre‐analytical effects exist and that it is essential to work towards unified standard operating procedures for blood sample collection, handling and storage.